Adhesion strength of flame sprayed ceramic coatings obtained by robotic projection - Seabra, Eurico; Silva, Luís; Aliew, Fuad; Sarmento, Joana Morais (Millenium - Journal of Education, Technologies, and Health, 2019)
Introduction: One of the possible applications of ceramic thermal barriers is in shells (permanent moulds – die casting). The moulds` capacity to support very high temperatures (up to 1600 °C) plays a crucial role in the selection of materials due to the liquid state of the cast iron. Objectives: This paper presents and discusses the obtained results from robotic flame projection tests, carried out with the purpose to quantify the influence of several factors of flame sprayed in the adhesion strength of coatings of Nickel-Aluminium-Molybdenum and Zirconium Oxide. In literature a minimum adhesion strength was not found for the application of thermal ceramic barriers in the coating of permanent casting moulds, so in this work it is intended to obtain its values ​​considering several combinations of projection parameters and substrates. Methods: The determination of the adhesion strength was performed according to the standard ASTM C633-79 where the coated test specimens were glued to CK45 steel against-specimens with a cyanoacrylate glue (LOCTITE 415). A weight of 100 N was then applied for 3 minutes to promote the initiation of the polymerization reaction of the cyanoacrylates and a period of 24 hours was needed so the bonded glue could acquire its maximum strength (sufficient enough to tear off the coating of the specimen). Finally tensile tests were carried out at the speed of 1 mm/min. Results: The main parameters studied are the material of the substrate, the projection angle and the substrate preheating temperature. The higher adhesion strength for the sprayed to 90° (average value of 6.2 MPa) was obtained by the specimens of spheroidal graphite cast iron (SGCI) with a preheating temperature of 120 °C. For the preheating of 90 °C and spray angle of 90° the aluminum-copper (AlCu) and brass specimens were the ones that obtained the higher adhesion strengths (average value of 4.5 MPa). The sprayed of 65° originates the higher adhesion strength in all the materials used for the substrate, being the highest value (average value of 8.3 MPa) obtained by the spheroidal graphite cast iron. Conclusions: The results obtained clearly suggest that the substrate material and the preheating temperature strongly influence the adhesion strength. The analysis of the coatings microstructures, using optical microscopy, supports this observation.